Technified, efficient, disabled bodies: notes on conventional and paralympic sport (PerCursos, 2025)
In contemporary times, the body is credited with achieving limitless progress, and among various practices, sport features prominently in this pursuit. The aim of this paper is to discuss how bodies perceived as disabled, while often marginalized, contribute something new to sport. We analyze some foundational aspects of this social practice and present exemplary cases of Paralympic athletes, examining how, through intense processes of technification and subjectivation aimed at producing bodily efficiency, we can conceive of dissonant corporealities. Our findings indicate that while high-performance sport serves as a societal model due to its aspirations, the Paralympic version still appears to exist on the periphery, perceived as a second-tier practice. The article also highlights similarities between conventional and non-standard sports in terms of organization and operation, suggesting that the body remains central to the construction of athletes' identities—both as a marker of power and as a reminder of pain and human finitude. Finally, regarding high-performance sport, our analysis shows that this practice for disabled individuals, despite potential advancements and achievements, tends to reinforce the structural model of the Olympic system. It also perpetuates existing interpretations and narratives, ultimately pointing to an ongoing ambiguity: whether the objective is performance or inclusive participation.
Keywords: education of body; technics; sport; paralympic games; olympic games